Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Berbantuan Media Wordwall terhadap Hasil Belajar IPAS Siswa Kelas IV di SDN 4 Kuranji - Aulia Salsabiela; Muhammad Makki; Aisa Nikmah Rahmatih (Mataram University, 2026)
This study was motivated by the low science learning outcomes of fourth-grade students at SDN 4 Kuranji, which were attributed to low learning motivation and limited student engagement due to the lack of variety in instructional media and the limited integration of technology in the learning process. This study aimed to determine the effect of the Teams Games Tournament (TGT) cooperative learning model assisted by Wordwall media on students' science learning outcomes in the topic